2015
DOI: 10.1007/s11605-014-2720-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Outcomes of Early Oral Feeding After Total Gastrectomy for Cancer

Abstract: BackgroundLittle data are available supporting the feasibility and safety of early oral feeding in patients after total gastrectomy. The aim of this study was to analyze the potential applicability of early provision of oral diet in these settings.MethodsMedical records of 353 patients who underwent total gastrectomy for gastric cancer between 2006 and 2012 were retrospectively analyzed. Early oral feeding was defined as clear liquid diet on postoperative day (POD) 1 followed by gradual introduction of solid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 21 publications
3
55
0
2
Order By: Relevance
“…In other series, substantial postoperative weight loss is associated with a lower likelihood of continuation of systemic chemotherapy and worse overall outcome. 7,15 A study of weight loss after gastrectomy by Lee and colleagues aimed to evaluate the association of weight loss with disease recurrence and survival. 8 The majority of patients underwent subtotal gastrectomy (71.9 %) for Stage I (59.3 %) gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other series, substantial postoperative weight loss is associated with a lower likelihood of continuation of systemic chemotherapy and worse overall outcome. 7,15 A study of weight loss after gastrectomy by Lee and colleagues aimed to evaluate the association of weight loss with disease recurrence and survival. 8 The majority of patients underwent subtotal gastrectomy (71.9 %) for Stage I (59.3 %) gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because the routine use of feeding tubes is not supported by prospective data and may be harmful, we place them only after a complication that prevents oral feeding. 4,5,15,16 Following gastrectomy, concerns about postoperative weight loss and nutritional deficits are motivating factors for the continued study of early postoperative enteral or parenteral nutrition. Our data suggest that not only can we predict significant postoperative weight loss based on the planned operation and baseline BMI, but also that the routine use of enteral feeding tubes is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Feng et al conducted the first RCT in patients undergoing total gastrectomy and demonstrated that ERAS including early oral nutrition could reduce morbidity and hospital stay. Subsequently, Sierzega et al demonstrated the advantages of early oral nutrition, including reduced hospital stay, in their retrospective analysis of 353 patients undergoing total gastrectomy. Our study provides reinforcing evidence that early oral nutrition may be safe and feasible in the subset of gastric cancer patients undergoing total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta‐analysis of 6 RCTs of gastric cancer surgery and a combined meta‐analysis of 15 RCTs and non‐RCTs of upper gastrointestinal surgery, early oral feeding (EOF) reduced the length of hospital stay and bowel recovery time, without increasing postoperative complications in patients undergoing gastrectomy. However, previous studies mostly focused on early oral nutrition after partial gastrectomy, and information on early oral nutrition after total gastrectomy is limited . Therefore, further investigation is required to demonstrate the safety and feasibility of early oral nutrition after total gastrectomy for gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent publications 1419 have described single institutional experiences with care pathways for gastric surgery patients. With the exception of a single report on total gastrectomies that showed a high rate of non compliance from clinical care pathways 18 , most reports describe decreases in length of stay following institution of standardized post-operative care.…”
Section: Discussionmentioning
confidence: 99%